2020
DOI: 10.1186/s12913-020-4992-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variations of licensed doctor distribution in China: measuring and mapping disparities

Abstract: Background: The licensed doctor misdistribution is one of the major challenges faced by China. However, this subject remains underexplored as spatial distribution characteristics (such as spatial clustering patterns) have not been fully mapped out by existing studies. To fill the void, this study aims to explore the spatio-temporal dynamics and spatial clustering patterns of different subtypes of licensed doctors (i.e., clinicians, traditional Chinese medicine doctors, dentists, public health doctors, general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Therefore, macro-regional factors possibly impact the flow of the health workforce. Based on previous studies ( 26 29 ) and data accessibility, we selected four categories of influential variables for health workforce allocation ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, macro-regional factors possibly impact the flow of the health workforce. Based on previous studies ( 26 29 ) and data accessibility, we selected four categories of influential variables for health workforce allocation ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the growing development of empirical spatial statistics had an impact on approaches available in the domain of the health workforce allocation. Previous studies have measured the geographic aggregation features of health workforce allocation using spatial techniques; while the majority has focused on demographical allocation ( 22 – 26 ), only few studies have taken account of the geographical allocation ( 11 , 27 ). Chen et al found the HRDI of health personnel presented with positive spatial autocorrelation; in other words, provinces with more intensive health personnel clustered, and vice versa ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the accessibility score was related to Shenzhen's internal economic strength, and the correlation analysis between GDP per capita and CHC accessibility score verifies this assumption (Table S2 in Supporting Information S1), there was a significant correlation between them (R 2 = 0.583, p < 0.01). In addition, licensed doctors play a critical role in healthcare resources (Zhu et al, 2020), we also illustrated the accessibility with the number of licensed doctors per 10,000 people as the CHC supply in Figure S2 in Supporting Information S1.…”
Section: Spatial Accessibility Evaluation Of Shenzhenmentioning
confidence: 99%
“…The distribution of midwives and rural health workers was assessed at 0.216 and 0.278. Relevant studies also focused on spatial variations of physicians (Zhu et al, 2022, Lin et al, 2021Stahlhut et al, 2021;You & Donnelly, 2022). Zhu et al (2022) conducted a study to unravel the licensed doctor misdistribution.…”
Section: Physician Workforce: Essential Role In Healthcare Deliverymentioning
confidence: 99%
“…Relevant studies also focused on spatial variations of physicians (Zhu et al, 2022, Lin et al, 2021Stahlhut et al, 2021;You & Donnelly, 2022). Zhu et al (2022) conducted a study to unravel the licensed doctor misdistribution. Using space-time scan statistics and Moran's I statistics, the authors explored the spatial variations in the temporal trends of licensed doctor density during 2012-2016.…”
Section: Physician Workforce: Essential Role In Healthcare Deliverymentioning
confidence: 99%